IMPLEMENTASI PROTONVPN UNTUK PENINGKATAN KEAMANAN AKSES ONEDRIVE PADA SISTEM OPERASI WINDOWS - Rakhmadi Rahman; Murtafia Murtafia (Jurnal Riset Sistem Informasi, 2026)
As reliance on cloud computing for data management grows, the issue of user data security when accessing services via public networks is a critical concern. This study investigates the implementation of the free-tier version of ProtonVPN on the Windows operating system as a mechanism to reinforce secure access to cloud platforms. ProtonVPN was selected for its offered high-level cryptographic protocols, user-friendly nature, and zero-cost availability. The methodology involved installation, connection configuration, and access testing on major cloud platforms (Google Drive and OneDrive). Results show that using the VPN effectively obfuscates the user's IP address and secures data traffic through encryption, significantly enhancing protection when interacting with cloud services. Despite limitations such as reduced speed performance and limited server choices, this solution proves efficient in elevating the security posture of cloud computing access on Windows devices.